Mini-Review of Laboratory Operations in Biobanking: Building Biobanking Resources for Translational Research - Cicek, Mine S.; Olson, Janet E. (Frontiers in Public Health, 2020)
Biobanks have become integral to improving population health. We are in a new era in medicine as patients, health professionals, and researchers increasingly collaborate to gain new knowledge and explore new paradigms for diagnosing and treating disease. Many large-scale biobanking efforts are underway worldwide at the institutional, national, and even international level. When linked with subject data from questionnaires and medical records, biobanks serve as valuable resources in translational research. A biobank must have high quality samples that meet researcher's needs. Biobank laboratory operations require an enormous amount of support—from lab and storage space, information technology expertise, and a laboratory management information system to logistics for sample movement, quality management systems, and appropriate facilities. A paramount metric of success for a biobank is the concept of every biospecimen coming to the repository belongs to a participant who has something to contribute to research for a healthier future. This article will discuss the importance of biorepository operations, specific to the collection and storage of participants materials. Specific focus will be given to maintaining the quality of samples, along with the various levels of support biorepositories need to fulfill their purpose and ensure the integrity of each specimen is maintained.